A Comparative Study of “Human Transcendental Identity” in the Thought of Heidegger and Mulla Sadrā - Mohammad Hossein Kiani (آموزه‌‌های فلسفه اسلامي)
Heidegger and Mulla Sadra’s views on the “transcendental identity of human” can be examined comparatively. In this comparison, conformities and differences are obtained. The forms of affinities are as follows: First, both believe in a single meaning of transcendence in the context of existence and acknowledge the unilateral influence of existence in the realization of human transcendence; Second, they believe in the importance of transcendence in the definition of human and consider the identity of human as dependent on transcendence and then, both imply the constant continuation of human transcendence. The points of distinction are as follows: First, their basis for transcendence is different; since the beginning of transcendence in Heidegger is with Descartes’ critique of subjectivism, and he arrives at the idea that man is the only being who realizes things in their opening; but the beginning of transcendence in Mulla Sadrā’s thought is depicted by explaining the objectivity (entity of connection) of beings to real existence and is based on the belief that the exploration of existence in man occurs through the substantial movement, will and grace of real existence. Second, Heidegger, with the ontological system he portrayed, believes in Dasein’s self-reliance in transcendence; but in Mulla Sadra’s thought, attention to the divinity and in the light of it, scientific and practical reliance on its aspects has fundamental importance.